2001
DOI: 10.4039/ent133549-4
|View full text |Cite
|
Sign up to set email alerts
|

Host–instar selection in the aphid parasitoid Monoctonus paulensis (Hymenoptera: Braconidae, Aphidiinae): assessing costs and benefits

Abstract: Females of Monoctonus paulensis (Ashmead), a solitary parasitoid of aphids, generally select the relatively smaller over equally available larger instars of the pea aphid, Acyrthosiphon pisum (Harris) (Hemiptera: Aphidoidea: Aphididae). Large hosts contain more resources for parasitoid development and hence have presumably higher quality; however, they require more time to subdue and are more likely to escape. We tested the hypothesis that a female’s choice among first (L1), second (L2), third (L3), and fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 43 publications
(43 reference statements)
2
41
0
2
Order By: Relevance
“…Per cent parasitism of A. ervi exposed to instars of A. pisum (20 individuals) resulted in second instar hosts producing the highest reproductive returns, with declining returns from younger and older instars (McBrien 1991). Similar patterns have been demonstrated with Lipolexis oregmae and Lysiphlebia mizari using Toxoptera citricida (Tsai & Wang 2002;Walker & Hoy 2003), Monoctonus paulensis using A. pisum (Chau & Mackauer 2001) and A. ervi using Myzus persicae (Colinet et al 2005). Intermediate instars represent a high-quality pool of future resources for koinobiotic parasitoids, because the larva continues to grow and develop with their hosts after parasitization.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Per cent parasitism of A. ervi exposed to instars of A. pisum (20 individuals) resulted in second instar hosts producing the highest reproductive returns, with declining returns from younger and older instars (McBrien 1991). Similar patterns have been demonstrated with Lipolexis oregmae and Lysiphlebia mizari using Toxoptera citricida (Tsai & Wang 2002;Walker & Hoy 2003), Monoctonus paulensis using A. pisum (Chau & Mackauer 2001) and A. ervi using Myzus persicae (Colinet et al 2005). Intermediate instars represent a high-quality pool of future resources for koinobiotic parasitoids, because the larva continues to grow and develop with their hosts after parasitization.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, adult aphids are large enough for parasitoid development; however, the larvae must compete with the host's embryos for resources, and adult aphids are thought to possess greater physiological resistance to parasitism (Walker & Hoy 2003;Colinet et al 2005). This can result in high larval or pupae mortality when parasitoid larvae develop in older aphids (Chau & Mackauer 2001;Walker & Hoy 2003;Colinet et al 2005;Henry et al 2005). For koinobiotic aphid parasitoids (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using a variety of aphid parasitoid species have shown that many species typically prefer the small and intermediate host instars for oviposition even though the larger host instars have more resources for the developing larvae (Kouame and Mackauer 1991;Mackauer et al 1996;Chau and Mackauer 2001;Tsai and Wang 2002;Colinet et al 2005). However, none of these studies have considered these results in light of optimal foraging theory.…”
Section: Introductionmentioning
confidence: 88%
“…Alguns modelos assumem que o desempenho (tamanho, desenvolvimento, razão sexual, fecundidade e longevidade) de um parasitóide está relacionado com o tamanho do hospedeiro no momento do parasitismo (Nicol & Mackauer 1999, Chau & Mackauer 2001. Entretanto, a relação entre as características do hospedeiro no momento do parasitismo e o ganho no desempenho do parasitóide não é linear e depende da combinação de vários fatores relacionados ao hospedeiro tais como, fi siologia e comportamento, qualidade da planta e ecologia nutricional (Mackauer et al 1996, Colinet et al 2005.…”
unclassified
“…Entretanto essa característica pode não ser necessariamente verdadeira para os parasitóides cenobiontes, como L. testaceipes, cujas larvas se desenvolvem enquanto os hospedeiros ainda se alimentam e crescem (Sequeira & Mackauer 1994, Chau & Mackauer 2001. Assim, o efeito do tamanho do hospedeiro no desempenho do parasitóide é mais difícil de predizer para cenobiontes do que para as espécies idiobiontes (Jenner & Kuhlmann 2006).…”
unclassified